Biblical Inerrancy and Depressive Symptoms - Krause, Neal M. (Pastoral psychology, 2018)
A number of investigators have studied biblical inerrancy (i.e., the belief that the Bible is inspired by God, free from error, and should be interpreted literally). However, there has been little research on the relationship between biblical inerrancy and mental health outcomes. The purpose of this study is to address this gap in the literature. This is accomplished by estimating a latent variable model that was designed to empirically evaluate the following relationships: (1) Blacks, people with less education, and conservative Christians are more likely to have a strong belief in biblical inerrancy; (2) people with a strong belief in biblical inerrancy are more likely to experience demonic spiritual struggles when they are faced with stressful events; (3) individuals who experience demonic spiritual struggles are more likely to feel that the sacred aspects of their lives have been threatened; and (4) greater sacred loss is associated with more depressive symptoms. Data from a recent nationwide survey (N = 2332) provide support for each of these relationships.